Researches on Surface of Near-field Optical Probe Based on Chemical Etching - Wang, Z.F.; Li, C.X. (Asian Journal of Chemistry, 2013)
Near-field scanning optical microscopy probes are produced according to classic Turner method. Temperature and etching system composed of different coverlayer and etchant mainly influence the fabrication of optical fiber probe in two ways: one is the etching velocity and the other is the change in the properties of the etching system. The diffusion of etchant in coverlayer can also affect the probes in the cone angle and yield. Probes fabricated after classic Turner method leads to rough surface of the taper, which is responsible for the formation of probe occurring at the interface of etchant and coverlayer.